Plasticizing Pregnancy: Microplastics Identified in Expectant Mothers' Feces - Uswatun Hasanah; Hasnawati Amqam; AR Ervina Septami; Maisuri Chalid; Ahmad Zaharin Aris (SAGE Publishing, 2024)
Introduction: Microplastics may be present in food and drinks from various sources, exposing pregnant women to these particles. Consumption of contaminated food can lead to the ingestion of microplastics by pregnant women, potentially causing adverse health effects on the fetus. This study aims to investigate the presence of microplastics in the stools of pregnant women. Methods: The research was conducted in the Makassar City region of South Sulawesi, Indonesia. Thirty healthy pregnant women from 2 community health centers, Pattingalloang and Jumpandang Baru, participated in the study. Their stools were analyzed using Fourier Transform Infrared (FTIR) microspectroscopy to detect the presence of microplastics. Result: The analysis revealed the presence of a total of 359 microplastics in the participants' stools, with particle counts ranging from 4 to 21 and sizes ranging from 0.2 to 4.9 mm per 25 g of stool. The polymers identified included Polyethylene Terephthalate (PET), Polyamide/Nylon, Polyethylene Chlorinated, HDPE, and Ethylene Propylene. The amount of microplastics varied significantly among groups with different levels of seafood consumption. Conclusion: Indonesian pregnant women have been exposed to some microplastic polymers.